Performance of Yeast Microbial Fuel Cell Integrated with Sugarcane Bagasse Fermentation for COD Reduction and Electricity Generation - Marcelinus Christwardana; J. Joelianingsih; Linda Aliffia Yoshi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
The purpose of this analysis is to evaluate the efficiency of the Microbial Fuel Cell (MFC) system incorporated with the fermentation process, with the aim of reducing COD and generating electricity, using sugarcane bagasse extract as a substrate, in the presence and absence of sugarcane fibers. There is a possibility of turning bagasse extract into renewable bioenergy to promote the sustainability of the environment and energy. As a result, the integration of liquid fermentation (LF) with MFC has improved efficiency compared to semi-solid state fermentation (S-SSF). The maximum power generated was 14.88 mW/m2, with an average COD removal of 39.68% per cycle. The variation margin of the liquid fermentation pH readings remained slightly decrease, with a slight deflection of +0.14 occurring from 4.33. With the absence of bagasse fibers, biofilm can grow freely on the anode surface so that the transfer of electrons is fast and produces a relatively high current. Experimental data showed a positive potential after an effective integration of the LF and MFC systems in the handling of waste. The product is then simultaneously converted into electrical energy. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).